A Systematic Review and Meta-Analysis of del Nido Versus Conventional Cardioplegia in Adult Cardiac Surgery. Issue 5 (October 2019) - An, Kevin R.; Rahman, Ishtiaq A.; Tam, Derrick Y.; Ad, Niv; Verma, Subodh; Fremes, Stephen E.; Latter, David A.; Yanagawa, Bobby
Objective: Del Nido cardioplegia (DC) has been used extensively in pediatric cardiac surgery but the efficacy and safety in adults remains uncertain. Our objective was to perform a systematic review and meta-analysis comparing DC and blood cardioplegia (BC) in our primary endpoint of 30-day or in-hospital mortality as well as other efficacy and safety endpoints. Methods: Both MEDLINE and EMBASE were searched from 1996 to 2017 for studies comparing DC and BC. Data were extracted by 2 independent investigators and aggregated in a random effects model. Results: One randomized controlled trial ( n = 89), 7 adjusted ( n = 1, 104), and 5 unadjusted observational studies ( n = 717) were included. There was no difference in in-hospital mortality between DC and BC (relative risk:0.67, 95% confidence interval [CI]: 0.22, 2.07; P = 0.49). DC reduced cardioplegia volume requirements (mean difference [MD]:−1.1 L, 95% CI, −1.6, −0.6; P < 0.0001), aortic cross-clamp time (MD: −8 minutes, 95% CI, −12, −3; P = 0.0004), and cardiopulmonary bypass (CPB) times (MD: −8 minutes, 95% CI, −14, −3; P = 0.03). DC reduced troponin release (standardized MD: −0.3, 95% CI, −0.5, −0.1; P = 0.001). In-hospital outcomes of stroke, atrial fibrillation, acute kidney injury/dialysis, low cardiac output state, blood transfusion, reoperation rate, postoperative left ventricular EF, intensive care unit length of stay (LOS), and in-hospital LOS were comparable between groups. Conclusions: DC is a safe alternative to BC in routine adult cardiac surgery. Its use is associated with reduction in CPB and aortic cross-clamp times and may potentially offer improved myocardial protection.